Analyzing User Experience in KAI Access Application using the UEQ Method - Maulidya, Icha; Salma, Cynthia Octavania Putri; Beda, Glorian Hilarius Kiantin; Barus, Irma Rasita Gloria; Fami, Amata (Universitas Trilogi, 2024)
This research aims to provide a comprehensive analysis of the User Experience (UX) components within the KAI Access platform framework, with a particular focus on the need to evaluate the platform's UX. This evaluation is very important because of the emergence of user complaints and usability problems in the KAI Access application rating on the Appstore and Playstore which can affect user satisfaction and overall user engagement. This study leverages insights from previous research in UX analysis, particularly in transportation applications, it identifies key areas for improvement. It implements best practices to ensure a smooth and intuitive user experience. Leveraging frameworks and theories from the field of UX design, the methodological approach revolves around conducting UEQ surveys to comprehensively understand user behavior and interactions. Through systematic evaluation, this research assesses the UX dynamics of the KAI Access system, by carefully examining the strengths, weaknesses, and areas that require improvement to increase user satisfaction and system usability. This research succeeded in showing that the KAI Access platform has good performance in terms of efficiency and reliability. However, from the evaluation there are deficiencies in various areas such as user interface design and interactive responsiveness which are shown in the discussion results indicating the potential for increasing user satisfaction and system usability through pragmatic improvements. Additionally, this paves the way for future research to explore the impact of these improvements on user satisfaction and consider the integration of new technologies for a richer user experience.